Effect of piecewise linear current waveforms on surge arrester residual voltage - Trotsenko, Yevgeniy; Brzhezitsky, Volodymyr; Masluchenko, Igor (Technology audit and production reserves, 2017)
The object of research is the magnitude and shape of the residual voltage that arises between the terminals of the surge arrester models when they are subjected to current and voltage pulses of a piecewise linear waveform. One of the most problematic places in this problem is the approximation of current switching pulses with a short duration and also steep front current pulses. With the help of the well-known double-exponential pulse, it is impossible to describe a pulse whose time-to-half duration is twice bigger the time-to-crest duration . At the same time, current pulses in the manufacturer catalogs of the surge arresters have exactly this ratio (1/2, 30/60 or 45/90 ). With the help of piecewise linear approximation, it is possible, bypassing complex calculations, to describe pulses of almost any shape, including switching current pulses and steep front current pulses. By means of evaluation version of Micro-Cap 11 circuit simulator the residual voltage on the surge arrester terminals is computed during a passage of the current pulses with different amplitude and wave shape. Current sources used in this research represent sources of simplified triangular (piecewise linear) current pulses. It is considered that the current wave rises linearly to its maximum value, and then also decays linearly to half its amplitude value. Comparison of the results suggests that proposed simplification of discharge current waveform has no significant effect on relative calculation error of residual voltage on surge arrester. If it is necessary to estimate only maximum value of residual voltage on surge arrester, it is possible to use piecewise linear approximation of switching and lightning currents with any amplitude and shape without loss of accuracy.